(untitled) (World Economics and Finance Bulletin, 2025)
In a competitive environment, brands have become an increasingly effective marketing tool because they encourage clients to discern between original products and counterfeit products and take actions based on more factual information. This article examines the role of Trademarks on small business and private entrepreneurship enterprises’ performance in Uzbekistan and important aspects of its development